Cultural diversity in Malaysia and the reconciliation for integration - Kartini Aboo Talib @ Khalid,; Shamsul Amri Baharuddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The clash between Hindu and Islam keeps them apart, but relatively Malaysia displays a moderate and tolerant model for both believers to live together and respect the mosque and the temple’s existence. The embedded Islam and the influence of Hinduism in the past resulted in the fusion of cultural mosaic that knits society. However, a few social deficits are stable tensions that may turn into conflict if they are ill-managed. Thus, the need to create and recreate a platform of integration is essential. The idea of preserving the cultural heritage, including the mosques and temples, the freedom to practice, and other fundamental rights protected by the Constitution, nurture the self-attachment feelings. This article applies a qualitative analysis using secondary data for historical narratives to discuss the social cohesion and reconciliation concepts about the cultural mosaic between Hinduism and Islam. In sum, the Federal Constitution, religious festivals, foods, and places are reconciliation processes to bridge the social cohesion gaps in a multiethnic society, packaged in tourism industries yet politically contested.